Longitudinal Study of Cellular and Systemic Cytokine Signatures to Define the Dynamics of a Balanced Immune Environment During Disease Manifestation in Zika Virus–Infected Patients. (16th April 2018) - Lum, Fok-Moon; Lye, David C B; Tan, Jeslin J L; Lee, Bernett; Chia, Po-Ying; Chua, Tze-Kwang; Amrun, Siti N; Kam, Yiu-Wing; Yee, Wearn-Xin; Ling, Wei-Ping; Lim, Vanessa W X; Pang, Vincent J X; et al.
Abstract : Understanding the host immune response during Zika virus (ZIKV) infection will provide valuable insights into ZIKV immunopathogenesis. In this study, characterization of cellular changes and immune mediators of ZIKV-infected patients was performed, allowing for the identification of key infection-associated markers. Abstract: Background: Since its unexpected reemergence, Zika virus (ZIKV) has caused numerous outbreaks globally. This study characterized the host immune responses during ZIKV infection. Methods: Patient samples were collected longitudinally during the acute, convalescence and recovery phases of ZIKV infection over 6 months during the Singapore outbreak in late 2016. Plasma immune mediators were profiled via multiplex microbead assay, while changes in blood cell numbers were determined with immunophenotyping. Results: Data showed the involvement of various immune mediators during acute ZIKV infection accompanied by a general reduction in blood cell numbers for all immune subsets except CD14 + monocytes. Importantly, viremic patients experiencing moderate symptoms had significantly higher quantities of interferon γ–induced protein 10, monocyte chemotactic protein 1, interleukin 1 receptor antagonist, interleukin 8, and placental growth factor 1, accompanied by reduced numbers of peripheral CD8 + T cells, CD4 + T cells, and double-negative T cells. Levels of T-cell associated mediators, including interferon γ–induced protein 10, interferon γ, and interleukin 10, were high in recovery phases of ZIKV infection, suggesting a functional role for T cells. The identification of different markers at specific disease phases emphasizes the dynamics of a balanced cytokine environment in disease progression. Conclusions: This is the first comprehensive study that highlights specific cellular changes and immune signatures during ZIKV disease progression, and it provides valuable insights into ZIKV immunopathogenesis.